Comb-like temperature-responsive polyhydroxyalkanoate-graft-poly(2-dimethylamino-ethylmethacrylate) for controllable protein adsorption. Issue 38 (12th September 2016) - Yao, Hui; Wei, Daixu; Che, Xuemei; Cai, Longwei; Tao, Lei; Liu, Lei; Wu, Linping; Chen, Guo-Qiang
Abstract : Polyhydroxyalkanoates (PHA) are a family of diverse biopolyesters produced by many bacteria grown on sustainable bio-resources such as glucose or fatty acids. Abstract : Polyhydroxyalkanoates (PHA) are a family of diverse biopolyesters produced by many bacteria grown on sustainable bio-resources such as glucose or fatty acids. A PHA copolymer P(3HDD- co -3H9D) consisting of 3-hydroxydodecanoate (3HDD) and 3-hydroxy-9-decenoate (3H9D) was synthesized by the engineered bacterium Pseudomonas entomophila . The PHA was used to generate a comb-like temperature-responsive graft polymer P(3HDD- co -3H9D)- g -poly(2-dimethylamino-ethylmethacrylate), abbreviated as (PHA- g -PDMAEMA), via a three-step reaction developed for this study. Uniform "side chain" PDMAEMA oligomers were first prepared via reversible addition–fragmentation chain transfer (RAFT) polymerization. Each PDMAEMA oligomer was subsequently added with a thiol group at the end of the chain via aminolysis. Thiol PDMAEMA was then grafted onto unsaturated P(3HDD- co -3H9D), with a tunable grafting density from 2.5 to 10 mol%. Graft copolymer PHA- g -PDMAEMA showed enhanced thermal stability, biocompatibility and controllable hydrophilicity compared with non-grafted P(3HDD- co -3H9D). The grafted material presented an obvious tendency of increasing protein adsorptions over the lower critical solution temperature (LCST 47.5 °C) on PHA- g -PDMAEMA with an increasing percentage of DMAEMA in the copolymers. At a temperature below LCST, PHA- g -PDMAEMA presented poor protein absorption in contrast to P(3HDD- co -3H9D). The temperature-responsive properties of the comb-like graft polymer PHA- g -PDMAEMA can be manipulated toward controllable protein adsorption for biomedical usages.